THE INFLUENCE OF PERCEIVED ENVIRONMENT SUPPORT ON EMPLOYEE PERFORMANCE WITH SELF-EFFICACY AS A MEDIATING VARIABLE ON MSMEs IN THE CENTRAL SURABAYA - Santoso, Olyvia Nathania; Lindawati, Tuty (Research In Management and Accounting (RIMA), 2024)
Employees are valuable assets owned by an organization or company, therefore, it is very important for companies, especially micro, small and medium enterprises (MSMEs) to be able to strive for maximum work results from these assets. Efforts to improve employee performance can be done in various ways, including by providing adequate environmental support, in the form of organizational support, supervisor support, peer support, and resource support, besides that, it can also be done by always paying attention to and encouraging employee Self-Efficacy, which is an employee's belief and confidence in their abilities. This study aims to determine the effect of Perceived Environment Support on Employee Performance with Self-Efficacy as the mediating variable. The technique and analysis method used in this research is PLS-SEM using the SmartPLS version 3.0 application. The object of this research is MSME employees in the Central Surabaya Region with a total sample of 137 respondents, most of them are 18-25 years old, and have worked for more than 1 year, and work in the culinary MSMEs business sector. The results of this study state that: 1) Perceived Environment Support has a positive and significant effect on Employee Performance, 2) Perceived Environment Support has a positive and significant effect on Self-Efficacy, 3) Self-Efficacy has a positive and significant effect on Employee Performance, and 4) Self-Efficacy has a positive effect as a mediating variable between Perceived Environment Support and Employee Performance.